Monitoreo e identificación de cambios de la vegetación del páramo a lo largo del gradiente altitudinal en la zona alta entre los 4590 a 4800 M.S.N.M de la reserva ecológica los Ilinizas. - Guerra Rondón Terry, Jose Luis (2023)
The present research project was developed along the altitudinal gradient in the upper area between 4590 to 4800 meters above sea level, with the aim of analyzing the change of the paramo vegetation along the altitudinal gradient in the Ilinizas Ecological Reserve, drawing 8 linear transects that were located every 30 altitudinal meters between 4590 to 4800 meters. These transects were divided by 10 quadrants, with a grid of 1m2 with microcuadrants of 10 cm2. The quadrants were 3 meters apart each until they were 100 meters long. The plant cover of the species was estimated by the Braun-Blanquet index that classifies into 7 categories that determine how much cover exists in the soil. It was possible to establish by species accumulation curves that in transect 9 there are 2 species, in transect number 10, yielded a result of only 1 species. With the transect 11, 12, 13, it was observed that there are 2 species that do not exceed 1% of coverage despite the presence of rocky material or adverse conditions that prevent the growth of species. In transect 14, there were 11 species, in 15 there were 10 species and transect 16 8 species were found. In the floristic composition the families with greater relative diversity are the Asteraceae and Caryophyllaceae. Simpson’s diversity index revealed that there are no dominant species, while comparative analyses by Sorensen and Jaccard showed that none of the transects are similar, although transect 9 and 10 share a single 1, since there is no uniformity of species. In addition, the conservation condition of the species discovered in the superparamo of the REI was examined, showing that there are 5 endemic species as "Least Concern" (LC), the Draba obovata is considered as a "Near Threatened" species (NT) and the species called Draba Aretioides, which is in Danger (EN), due to its presence in the Andean highlands of Ecuador. Based on the results, it was evident that the composition of the species varies as we climb from 4590 to 4800 meters above sea level, could be that there are adverse environmental conditions or there are no facilities for the few species that were found to grow or adapt to those conditions.